Solid electrolyte and preparation method and application thereof
By introducing nano SiO2 particles and polyacrylonitrile (PAN) into the solid electrolyte, the growth of lithium dendrites is suppressed by using the electrochemical microbattery mechanism, the problem that existing solid electrolytes cannot prevent lithium dendrites is solved, and higher ionic conductivity and cyclic stability are achieved.
Patent Information
- Application Number
- CN202510036614.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
AI Technical Summary
Existing solid electrolytes cannot fundamentally prevent the production of lithium dendrites. When the current is higher than the critical current density, dendrites can still pierce the electrolyte, causing a battery to short-circuit.
Using a composite solid electrolyte composed of nano SiO2 particles, polyacrylonitrile (PAN) and polyethylene oxide (PEO), the nano SiO2 particles inhibit the growth of lithium dendrites through the electrochemical microbattery mechanism, and form Li3N and LiF through PAN to improve interface stability.
It significantly improves the ionic conductivity and high voltage resistance of the solid electrolyte, effectively inhibits the growth of lithium dendrites, reduces the risk of battery short circuits, and improves cycling stability.
Smart Images

Figure CN119905646A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolyte materials and preparation methods thereof, and in particular to a solid electrolyte and a preparation method and application thereof. Background Art
[0002] Since the invention of the first battery, people have never stopped pursuing high energy density electrochemical energy storage systems. Lithium metal batteries are considered to be the most ideal high energy density battery system due to their extremely high theoretical specific capacity and lowest reduction potential. However, many problems such as dendrite growth on the lithium anode side and instability of the solid electrolyte interface (SEI) have seriously affected the cycle performance and safety of lithium metal batteries, hindering the practical application of lithium metal batteries.
[0003] It is generally believed that lithium dendrites are caused by uneven distribution of space charge, differences in current density on the anode surface, and cracks in the solid electrolyte interface (SEI). Based on the growth mechanism of lithium dendrites, a lot of research has been done on preventing the parasitic growth of lithium dendrites, such as structural anodes and electrolyte / electrode interface modifications. However, the above solutions can only alleviate dendrite growth to a certain extent and extend the safe life of the battery. Lithium dendrites are inevitably produced during long-term operation of lithium metal batteries. At present, it is generally believed that the use of solid electrolytes is an important method to inhibit lithium dendrites, because they have mechanical properties that other electrolytes cannot match. High modulus and high strength allow solid electrolytes to resist sharp dendrites, giving the battery higher safety performance. However, solid electrolytes still cannot fundamentally prevent the generation of lithium dendrites. When the current is higher than the critical current density, lithium dendrites can still pierce the electrolyte, thereby short-circuiting the battery. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a solid electrolyte and its preparation method and application, aiming to solve the technical problem that the existing solid electrolytes cannot fundamentally prevent the generation of lithium dendrites, and when the current is higher than the critical current density, the dendrites can still pierce the electrolyte, thereby causing the battery to short-circuit.
[0005] In a first aspect, an embodiment of the present application provides a solid electrolyte comprising a lithium salt, nano-SiO2 particles, polyacrylonitrile (PAN) and an organic polymer matrix, wherein the mass percentage of the nano-SiO2 particles is 5% to 20%.
[0006] In the technical solution of the embodiment of the present application, the present application uses nano-scale inorganic ceramic particles SiO2 as fillers to construct a high-performance PEO-based composite solid electrolyte, which solves the problem of lithium dendrites in long-term charging and discharging operation. On the one hand, this nano-SiO2 particle filler can effectively inhibit the crystallization of the polymer matrix PEO, provide more ion conductive channels, and significantly improve the ion conductivity of the solid electrolyte; on the other hand, once the nano-SiO2 particles in the composite solid electrolyte contact the generated lithium dendrites, an electrochemical micro-battery will be formed. In this micro-battery reaction, the lithium dendrites as the battery anode will be oxidized and cracked at a higher rate, thereby greatly eliminating the further growth of lithium dendrites and possible short circuit phenomena. Since a stable interface is a necessary condition for the growth of lithium dendrites, the present application accordingly proposes a strategy for the formation of an overall stable interface structure and the in-situ elimination of dendrites, that is, in addition to nano-SiO2 particles, PAN is also introduced as an additive to inhibit lithium dendrite solid electrolytes. The introduction of PAN will form Li3N and LiF as good lithium ion conductors, thereby promoting the stability of lithium ions at the interface.
[0007] In some embodiments, the organic polymer matrix includes polyethylene oxide (PEO), the EO group in PEO and the Li + The molar ratio is (15~25):1.
[0008] In some embodiments, the mass ratio of PAN to PEO is (0.5-1.5):4.
[0009] In some embodiments, the particle size of the nano-SiO2 particles is 100-150 nm.
[0010] In some embodiments, the lithium salt is one or both of LiTFSI and LiPF6.
[0011] In a second aspect, the present invention provides a method for preparing a solid electrolyte, comprising the following steps: S1, stirring and mixing the lithium salt and the solvent to disperse the lithium salt in the solvent to obtain a first mixed solution; S2, dispersing the nano-SiO2 particles in the first mixed solution by ultrasonication to obtain a second mixed solution; S3, adding PEO and PAN to the second mixed solution, heating and stirring to obtain a third mixed solution; S4. Evenly apply the third mixed liquid on a polytetrafluoroethylene plate, heat and dry it to obtain a solid electrolyte.
[0012] In some embodiments, the solvent is one or both of DMF and G4.
[0013] In some embodiments, in step S1, the lithium salt is dispersed in the solvent by magnetic stirring, and the rotation speed of the magnetic stirring is 550-650 r / min.
[0014] In some embodiments, the heating temperature in step S3 is 50-60°C.
[0015] In some embodiments, the heating and drying step in step S4 includes: first vacuum drying at 50-60° C. for 48 hours, then raising the temperature to 80-90° C. and continuing drying for 6 hours.
[0016] In a third aspect, an embodiment of the present application provides a lithium metal battery including a solid electrolyte.
[0017] Different from the existing technical solutions, the beneficial effects of this application include: 1. In order to inhibit the growth of lithium dendrites, the present application designs a solid electrolyte composed of inorganic ceramic filler nano-SiO2 particles, organic additive PAN and organic polymer matrix PEO. In the solid electrolyte, PAN and lithium salt can form Li3N and LiF. Li3N is a superionic conductor, and its presence helps Li + The rapid transfer of LiF and the reduction of interfacial resistance; LiF shows low electrical conductivity and excellent electrochemical stability, which inhibits further reactions between the electrolyte and the lithium sheet, thereby improving the interfacial stability. The introduction of nano-SiO2 particles not only reduces the glass transition temperature of the solid electrolyte, but also significantly improves the high-voltage resistance of the solid electrolyte. In addition, the added nano-SiO2 particles can inhibit the growth of lithium dendrites and decompose the generated lithium dendrites through the mechanism of electrochemical microbatteries. This "SiO2-PAN" composite doping strategy significantly improves the electrochemical performance compared to single doping fillers or additives, and will provide a new solution for the development of solid-state lithium batteries with high cycle stability.
[0018] 2. This application optimizes the mixing ratio of nano-SiO2 particles in the solid electrolyte. Through characterization methods such as XRD and EDS, this application studies the effect of different nano-SiO2 particle doping amounts on the crystallinity of PEO solid electrolyte. The results show that when 5wt%~20wt% nano-SiO2 particles are doped into the electrolyte, the interfacial compatibility between the solid electrolyte and the lithium metal negative electrode is better. This application believes that this is mainly due to the fact that the filler inhibits the crystallization of the electrolyte matrix PEO, and the agglomeration phenomenon between the nano-SiO2 particles is not obvious, which improves the ionic conductivity of the electrolyte.
[0019] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 Schematic diagram of the formation mechanism of lithium dendrites in the solid electrolyte of the present application embodiment; Figure 2 A schematic diagram of the mechanism of lithium oxidation dissolution in a solid electrolyte through an electrochemical microbattery mechanism in an embodiment of the present application; Figure 3 A schematic diagram of lithium dendrites suppressed after microbattery reaction in a solid electrolyte according to an embodiment of the present application; Figure 4 XRD diagrams of PEO-based solid electrolyte materials of Example 1, Example 2, and Comparative Example 1 of the present application; Figure 5 a is the EDS spectrum analysis of the chemical composition of the PEO-based solid electrolyte in Example 1 of the present application as the Si element changes, Figure 5 b is the EDS spectrum analysis of the chemical composition of the PEO-based solid electrolyte in Example 2 as the Si element changes; Figure 6 For the current density of the PEO-based solid electrolyte material in Examples 1 and 2 of this application, the current density is from 0.1 to 0.4 mA·cm −2 Voltage distribution curve when . DETAILED DESCRIPTION
[0022] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0024] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0027] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0028] It is generally believed that the use of solid electrolytes is an important method to inhibit lithium dendrites, because it has mechanical properties that other electrolytes cannot match. The high modulus and high strength allow solid electrolytes to resist sharp dendrites, making the battery safer. However, solid electrolytes still cannot fundamentally prevent the generation of lithium dendrites. When the current is higher than the critical current density, lithium dendrites can still pierce the electrolyte, causing the battery to short-circuit.
[0029] In order to solve the technical problem that the existing solid electrolyte cannot fundamentally prevent the generation of lithium dendrites, and when the current is higher than the critical current density, the dendrites can still pierce the electrolyte, thereby causing the battery to short-circuit, the present application provides a solid electrolyte and its preparation method and application, wherein the present application designs a solid electrolyte composed of inorganic ceramic filler nano-SiO2 particles, organic additive PAN and polymer matrix PEO to inhibit the growth of lithium dendrites. In the solid electrolyte, PAN and lithium salt can form Li3N and LiF, thereby enhancing the interface stability, promoting lithium ion transport, enhancing the interface compatibility between the electrolyte and the lithium sheet, and improving the cycle stability of the battery. The introduction of nano-SiO2 particles not only reduces the glass transition temperature of the solid electrolyte, but also significantly improves the high pressure resistance of the solid electrolyte. In addition, the added nano-SiO2 particles can inhibit the growth of lithium dendrites through the mechanism of electrochemical microbatteries and decompose the generated lithium dendrites. This "SiO2-PAN" composite doping strategy significantly improves the electrochemical performance compared to single doping fillers or additives, and will open up new solutions for the development of high cycle stability solid lithium batteries.
[0030] In a first aspect, an embodiment of the present application provides a solid electrolyte comprising a lithium salt, nano-SiO2 particles, polyethylene oxide (PEO) and polyacrylonitrile (PAN), wherein the mass percentage of the nano-SiO2 particles is 5% to 20%.
[0031] In some embodiments, the organic polymer matrix includes polyethylene oxide (PEO), the EO group in PEO and the Li + The molar ratio is (15~25):1.
[0032] In the technical solution of the embodiment of the present application, PEO is widely studied as a solid electrolyte for lithium metal batteries due to its excellent salt solvation ability, high dielectric constant and electrode interface compatibility. Although the traditional PEO solid electrolyte can resist the sharp dendrites, making the battery have higher safety performance, its high crystallinity leads to relatively low ionic conductivity; and it still cannot fundamentally prevent the generation of lithium dendrites. When the current is higher than the critical current density, the dendrites can still pierce the electrolyte, thereby short-circuiting the battery. The present application uses nano-scale inorganic ceramic particles SiO2 as filler to construct a high-performance PEO-based composite solid electrolyte, which solves the problem of lithium dendrites in long-term charging and discharging operation. On the one hand, this nano-SiO2 particle filler can effectively inhibit the crystallization of the polymer matrix PEO, provide more ion conduction channels, and significantly improve the ion conductivity of the solid electrolyte; on the other hand, once the nano-SiO2 particles in the composite solid electrolyte come into contact with the generated lithium dendrites, an electrochemical microbattery will be formed. In this microbattery reaction, the lithium dendrites as the battery anode will be oxidized and cracked at a higher rate, thereby greatly eliminating the further growth of lithium dendrites and possible short circuits. Since a stable interface is a necessary condition for the growth of lithium dendrites, the present application accordingly proposes a strategy for the formation of an overall stable interface structure and the in-situ elimination of dendrites, that is, in addition to nano-SiO2 particles, PAN is also introduced as an additive to the solid electrolyte to inhibit lithium dendrites. The introduction of PAN will form Li3N and LiF as good lithium ion conductors, thereby promoting the stability of lithium ions at the interface.
[0033] like Figures 1 to 3 As shown in the figure, when lithium dendrites first come into contact with nano-SiO2 particles, they will form a micro-battery with the nano-SiO2 particles, and the lithium will be oxidized into lithium ions. The lithium ions react with SiO2 to form lithium silicon, thereby inhibiting the continued growth of dendrites and increasing the safety of the battery. The specific reaction process is as follows: Li→Li + +e - 5SiO2+4Li + +4e - →2Li2Si2O5+Si Si+xLi + +xe - →Li x Four.
[0034] At the same time, adding an appropriate amount of nano-SiO2 particles (5wt%~20wt%) can significantly inhibit the crystallization of the polymer matrix PEO, provide more ion-conducting channels, and thus significantly increase the ion conductivity of the electrolyte, while also avoiding agglomeration and blocking the ion diffusion path. Nano-SiO2 particles may expand in volume during the charge and discharge process. Therefore, in the absence of PAN's flexible support, excessive nano-SiO2 particle fillers may cause the electrolyte to lack the flexibility to accommodate this volume change, resulting in structural instability of the battery.
[0035] In some embodiments, the mass ratio of PAN to PEO is (0.5-1.5):4.
[0036] In the technical solution of the embodiment of the present application, an appropriate amount of PAN can promote the stability of lithium ions at the interface, but the PAN molecular structure contains a large number of non-ionic groups, and too much PAN will occupy the space in the solid electrolyte, hindering the movement of ions, thereby reducing the ion conductivity. The flexibility of the PAN molecular chain will make the electrolyte too soft, and too high a PAN content may cause the mechanical properties of the electrolyte to deteriorate, making it easy to deform or damage.
[0037] In some embodiments, the particle size of the nano-SiO2 particles is 100-150 nm.
[0038] In some embodiments, the lithium salt is one or both of LiTFSI and LiPF6.
[0039] In a second aspect, an embodiment of the present application provides a method for preparing a solid electrolyte, comprising the following steps: S1, stirring and mixing the lithium salt and the solvent to disperse the lithium salt in the solvent to obtain a first mixed solution; S2, dispersing the nano-SiO2 particles in the first mixed solution by ultrasonication to obtain a second mixed solution; S3, adding PEO and PAN to the second mixed solution, heating and stirring to obtain a third mixed solution; S4. Evenly apply the third mixed liquid on a polytetrafluoroethylene plate, heat and dry it to obtain a solid electrolyte.
[0040] In some embodiments, the solvent is one or both of DMF and G4.
[0041] In some embodiments, in step S1, the lithium salt is dispersed in the solvent by magnetic stirring, and the rotation speed of the magnetic stirring is 550-650 r / min.
[0042] In some embodiments, the heating temperature in step S3 is 50-60°C.
[0043] In some embodiments, the heating and drying step in step S4 includes: first vacuum drying at 50-60° C. for 48 hours, then raising the temperature to 80-90° C. and continuing drying for 6 hours.
[0044] In a third aspect, an embodiment of the present application provides a lithium metal battery including a solid electrolyte.
[0045] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0046] 1. Preparation method Example 1 (1) LiTFSI, PEO, and PAN were first dried in a vacuum oven for 12 h to remove moisture from the materials.
[0047] (2) First, 1.30 g of lithium salt LiTFSI was weighed and placed in 10 mL of DMF solvent and dissolved rapidly under the action of a magnetic stirrer at a stirring rate of 600 r / min.
[0048] (3) Then, 0.7 g of nano-SiO2 particles were weighed and evenly dispersed in the solution containing lithium salt by ultrasound.
[0049] (4) Then, 4 g PEO and 1 g PAN were weighed and added to the mixed solution. The mixture was stirred in a 60 °C water bath for 24 h to mix all the substances into a uniform slurry.
[0050] (5) Next, the mixed slurry was evenly spread on a polytetrafluoroethylene plate with a scraper. The sample was then placed in a leveled vacuum drying oven and dried at 60 °C for 48 h. Then, the temperature was raised to 80 °C for 6 h to allow the solvent DMF to fully evaporate, thereby obtaining a solid electrolyte.
[0051] Example 2 Compared with Example 1, the only difference is that the amount of nano-SiO2 particles is increased, and the rest remains unchanged, as follows: (1) LiTFSI, PEO, and PAN were first dried in a vacuum oven for 12 h to remove moisture from the materials.
[0052] (2) First, 1.30 g of lithium salt LiTFSI was weighed and placed in 10 mL of DMF solvent and dissolved rapidly under the action of a magnetic stirrer at a stirring rate of 600 r / min.
[0053] (3) Then, 1.58 g of nano-SiO2 particles were weighed and uniformly dispersed in the solution containing lithium salt by ultrasound.
[0054] (4) Then, 4 g PEO and 1 g PAN were weighed and added to the mixed solution. The mixture was stirred in a 60 °C water bath for 24 h to mix all the substances into a uniform slurry.
[0055] (5) Next, the mixed slurry was evenly spread on a polytetrafluoroethylene plate with a scraper. The sample was then placed in a leveled vacuum drying oven and dried at 60 °C for 48 h. Then, the temperature was raised to 80 °C for 6 h to allow the solvent DMF to fully evaporate, thereby obtaining a solid electrolyte.
[0056] Example 3 Compared with Example 1, the only difference is that the amount of nano-SiO2 particles is reduced, and the rest remains unchanged, as follows: (1) LiTFSI, PEO, and PAN were first dried in a vacuum oven for 12 h to remove moisture from the materials.
[0057] (2) First, 1.30 g of lithium salt LiTFSI was weighed and placed in 10 mL of DMF solvent and dissolved rapidly under the action of a magnetic stirrer at a stirring rate of 600 r / min.
[0058] (3) Then, 0.33 g of nano-SiO2 particles were weighed and evenly dispersed in the solution containing lithium salt by ultrasonication.
[0059] (4) Then, 4 g PEO and 1 g PAN were weighed and added to the mixed solution. The mixture was stirred in a 60 °C water bath for 24 h to mix all the substances into a uniform slurry. (5) Next, the mixed slurry was evenly spread on a polytetrafluoroethylene plate with a scraper. The sample was then placed in a leveled vacuum drying oven and dried at 60 °C for 48 h. Then, the temperature was raised to 80 °C for 6 h to allow the solvent DMF to fully evaporate, thereby obtaining a solid electrolyte.
[0060] Comparative Example 1 Compared with Example 1, the only difference is that no nano-SiO2 particles are added, and the rest remain unchanged, as follows: (1) LiTFSI, PEO, and PAN were first dried in a vacuum oven for 12 h to remove moisture from the materials.
[0061] (2) First, 1.30 g of lithium salt LiTFSI was weighed and placed in 10 mL of DMF solvent and dissolved rapidly under the action of a magnetic stirrer at a stirring rate of 600 r / min.
[0062] (3) Then, 4 g PEO and 1 g PAN were weighed and added to the mixed solution. The mixture was stirred in a 60 °C water bath for 24 h to mix all the substances into a uniform slurry.
[0063] (4) Next, the mixed slurry was evenly coated on a polytetrafluoroethylene plate with a scraper. The sample was then placed in a leveled vacuum drying oven and dried at 60 °C for 48 h. Then, the temperature was raised to 80 °C for 6 h to allow the solvent DMF to fully evaporate, thereby obtaining a solid electrolyte.
[0064] Comparative Example 2 Compared with Example 1, the only difference is that PAN is not added, and the rest remains unchanged, as follows: (1) LiTFSI and PEO were first dried in a vacuum oven for 12 h to remove moisture from the materials.
[0065] (2) First, 1.30 g of lithium salt LiTFSI was weighed and placed in 10 mL of DMF solvent and dissolved rapidly under the action of a magnetic stirrer at a stirring rate of 600 r / min.
[0066] (3) Then, 0.7 g of nano-SiO2 particles were weighed and evenly dispersed in the solution containing lithium salt by ultrasound.
[0067] (4) Then, 4 g of PEO was weighed and added to the mixed solution. The mixture was stirred in a 60 °C water bath for 24 h to allow all substances to be mixed into a uniform slurry.
[0068] (5) Next, the mixed slurry was evenly spread on a polytetrafluoroethylene plate with a scraper. The sample was then placed in a leveled vacuum drying oven and dried at 60 °C for 48 h. Then, the temperature was raised to 80 °C for 6 h to allow the solvent DMF to fully evaporate, thereby obtaining a solid electrolyte.
[0069] 2. Test Method The PEO composite solid electrolyte prepared in the above example was tested for ionic conductivity.
[0070] Assembly of the battery for testing ionic conductivity: The solid electrolyte was cut into a circular shape of appropriate size in the glove box, and then assembled into a button cell of SS / electrolyte membrane / SS (SS is stainless steel). Before the test, the button cell was stabilized at 60°C for 3h to obtain good contact between the electrolyte and the electrode, and then kept at room temperature overnight. The frequency was selected to be 0.1 Hz~1 MHz, the amplitude voltage was 10 mV, and the electrochemical impedance spectroscopy was used to test the ionic conductivity.
[0071] III. Analysis of test results of various embodiments and comparative examples (1) The ionic conductivity of the solid electrolytes prepared in each embodiment and comparative example was tested. The test results are shown in Table 1 below.
[0072] Table 1 Test results of ionic conductivity of solid electrolytes prepared in various embodiments and comparative examples
[0073] As can be seen from Table 1, when the doping amount of nano-SiO2 particles is 10wt%, the best effect on improving the ionic conductivity of the solid electrolyte is achieved. Too high or too low a doping amount of nano-SiO2 particles will result in a decrease in ionic conductivity. There are several reasons for this: (1) Ion transport path. The addition of filler nano-SiO2 particles can significantly inhibit the crystallization of the polymer matrix PEO and provide more ion-conducting channels, which will significantly increase the ionic conductivity of the solid electrolyte. However, excessive doping may in turn block the ion diffusion path. (2) Local electrochemical micro-battery mechanism. When lithium dendrites first come into contact with nano-SiO2 particles, they will form micro-batteries with the nano-SiO2 particles. Lithium will be oxidized to lithium ions, thereby inhibiting the continued growth of dendrites and increasing the safety of the battery. (3) There is no obvious agglomeration between particles. When the doping amount of nano-SiO2 particles is high, the aggregation of nano-SiO2 particles will reduce the interface area that is conducive to ion migration, which is very unfavorable for ion transport. Therefore, when the addition amount of nano-SiO2 particles is 10wt%, multiple factors such as crystal structure, ion transmission path, and interface layer properties reach an optimal balance, which maximizes the overall improvement of the ionic conductivity of the composite solid electrolyte.
[0074] As can be seen from Table 1, the absence of PAN in Comparative Example 2 will also lead to a significant decrease in ionic conductivity. This is because if the plasticizer PAN is not added, the crystallinity of PEO at room temperature can reach 75%-80%, which will lead to difficulty in chain segment movement, low ionic conductivity, and poor mechanical strength.
[0075] (2) XRD scanning was performed on the PEO-based solid electrolyte materials in Example 1, Example 2 and Comparative Example 1. Figure 4As shown, the characteristic peaks of the PEO matrix are at 19.1° and 23.3°. Compared with the sample of Comparative Example 1, the peak intensities of the samples of Example 1 and Example 2 with the addition of nano-SiO2 particles are significantly reduced, which indicates that the addition of filler nano-SiO2 particles can significantly inhibit the crystallization degree of the matrix; secondly, we found that when the proportion of nano-SiO2 particles added in Example 2 is 20%, the intensity of the characteristic peak is lower than that of the sample of Example 1 when the proportion of nano-SiO2 particles added is 10%, which indicates that the crystallinity of the sample of Example 2 is lower. This is because the presence of a large number of nano-SiO2 particles hinders the orderly arrangement of the molecular chains, thereby inhibiting the crystallization of the matrix, which is very beneficial to the improvement of ionic conductivity.
[0076] (3) Perform EDS scanning on the PEO-based solid electrolyte materials in Example 1 and Example 2. Figure 5 As shown in a, in the electrolyte of Example 1, the distribution of Si element is relatively uniform, which shows that the nano-SiO2 particles we added are evenly dispersed in the matrix, which lays the foundation for the subsequent application of the electrolyte, because the uniform distribution of fillers can provide a uniform ion transmission path, so that lithium ions can be evenly deposited on the electrode, which is the premise for inhibiting the formation of dendrites. Figure 5 As shown in Figure b, in the electrolyte of Example 2, with the increase in the content of nano-SiO2 particles, obvious agglomeration occurs between the particles, and the aggregation of particles reduces the interface area that is conducive to ion migration, which is very unfavorable to the transmission of ions.
[0077] (4) The voltage distribution curve of the PEO-based solid electrolyte material in Example 1 and Example 2 is tested. Figure 6 As shown in Figure 2, at low current density, both batteries can operate stably, but the polarization potential generated by the Li|20%-PPS|Li battery in Example 2 is higher than that of the Li|10%-PPS|Li battery in Example 1. As the current density continues to increase, at 0.3 mA / cm 2 At a current density of 0.3 mA / cm, the Li|20%-PPS|Li battery in Example 2 produced a permanent short circuit after cycling for 60 hours, but for the Li|10%-PPS|Li battery in Example 1, a permanent short circuit occurred at a current density of 0.3 mA / cm 2 When the current increases to 0.4 mA / cm 2 When the battery is charged, a large polarization occurs, and the polarization phenomenon is aggravated with the cycle, and finally the battery short-circuit occurs. The solid electrolyte in Example 1 has a better effect of inhibiting lithium dendrites. We attribute the short circuit of the battery to the growth of dendrites. After the electrolyte is completely pierced by the dendrites, the battery short-circuit occurs.
[0078] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A solid electrolyte, characterized in that The invention comprises lithium salt, nano-SiO2 particles, PAN and an organic polymer matrix, wherein the mass percentage of the nano-SiO2 particles is 5% to 20%.
2. The solid electrolyte according to claim 1, characterized in that The organic polymer matrix includes PEO, the EO group in the PEO and the Li + The molar ratio is (15~25):
1.
3. The solid electrolyte according to claim 2, characterized in that The mass ratio of PAN to PEO is (0.5~1.5):
4.
4. The solid electrolyte according to claim 1, characterized in that The particle size of the nano-SiO2 particles is 100-150 nm.
5. The solid electrolyte according to claim 1, characterized in that The lithium salt is one or both of LiTFSI and LiPF6.
6. A method for preparing a solid electrolyte according to any one of claims 1 to 5, characterized in that: The steps include: S1, stirring and mixing the lithium salt and the solvent to disperse the lithium salt in the solvent to obtain a first mixed solution; S2, dispersing the nano-SiO2 particles in the first mixed solution by ultrasonication to obtain a second mixed solution; S3, adding PEO and PAN to the second mixed solution, heating and stirring to obtain a third mixed solution; S4, evenly coating the third mixed solution on a polytetrafluoroethylene plate, heating and drying, to obtain a solid electrolyte.
7. The method for preparing a solid electrolyte according to claim 6, characterized in that: The solvent is one or two of DMF and G4.
8. The method for preparing a solid electrolyte according to claim 6, characterized in that: The heating temperature in step S3 is 50-60°C.
9. The method for preparing a solid electrolyte according to claim 6, characterized in that: The heating and drying step in step S4 includes: first vacuum drying at 50-60° C. for 48 hours, then raising the temperature to 80-90° C. and continuing drying for 6 hours.
10. A lithium metal battery, characterized in that: The invention comprises the solid electrolyte according to any one of claims 1 to 5.
Citation Information
Cited By
Composite electrode with positive plate supporting double-layer polymer electrolyte membrane and preparation method of composite electrode
CN122418065A